COMPARATIVE RESEARCH ON CONJUNCTIONS EXPRESSING CAUSE AND REASON IN ENGLISH AND UZBEK - O‘rinova Zohidaxon Adhamjon qizi; Vohidova Tamanno Saidjonovna (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The article describes the features of a comparative study of conjunctions expressing cause and reason in English and Uzbek, their structural and semantic relations in complex sentences with subordinate clauses of condition in English and Uzbek.The author of the article analyzes the unions of cause and reason and reveals additional shades of semantic relations expressed by other unions that go in the meaning of cause or reason on the example of the texts of English-language newspapers and magazines. The study shows that in 80% the use of conjunctions of cause and reason is similar in English and Uzbek grammar, and with the correct translation and selection of equivalents, only 60% of the similarity is determined.